Interference in Wireless Networks: Causes, Analyses and Practical Mitigating Techniques - Oudah, Ali A.; A., Hameed (Canadian Center of Science and Education, 2014)
This paper addresses the key characteristics of interference in wireless networks. Moreover, it considers the impact of interference from Code Division Multiple Access base station to Wideband-Code Division Multiple Access one. A detailed discussion of major interference mitigation techniques in wireless networks, in general, and CDMA and W-CDMA systems, in particular is also imparted on. The techniques and findings in this paper can be easily used in the analyses of other wireless technologies.